Method for measuring inorganic oxide sample

JP2025034813APending Publication Date: 2025-03-13SUMITOMO METAL MINING CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023141444
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0013】 本発明によれば、無機酸化物試料の軟化点を精度よく、かつ再現性高く測定することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034813000001_ABST
    Figure 2025034813000001_ABST
Patent Text Reader

Abstract

To measure the softening point of an inorganic oxide sample with accuracy and high reproducibility.SOLUTION: A method for measuring inorganic oxide sample has: a preparation step of preparing an inorganic oxide sample; a pulverization step of pulverizing the inorganic oxide sample to form a powder sample; a filling step of filling the powder sample into a heat-resistant container having an opening, and mounting a pressure lid having an area 0.3 times or more and 0.9 times or less the area of the opening; a measurement step of providing the heat-resistant container filled with the powder sample for a thermomechanical analysis apparatus, heating the powder sample while giving a load from above the pressure lid to acquire a thermomechanical analysis curve showing the relation between the temperature of the powder sample and a change of the position of the pressure lid due to heat deformation, and measuring the softening point of the inorganic oxide sample on the basis of the thermomechanical analysis curve.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for measuring an inorganic oxide sample. [Background technology]

[0002] For example, metal components (metals) such as Ni may be recovered from ores by dry smelting. In this case, in order to check the quality of the smelting process, it is important to understand the softening point of the slag, which is an inorganic oxide separated from the metal components. The lower the softening point of the slag, the larger the metal particles such as Ni can be reduced and precipitated, improving the smelting efficiency, such as the recovery rate.

[0003] As a method for measuring the melting point of inorganic oxide samples such as slag, for example, there is a method for detecting the endothermic reaction during melting using a Thermogravimetry-Differential Thermal Analysis (TG-DTA) or a Differential Scanning Calorimeter (DSC). However, unlike metals, inorganic oxides absorb less heat and melt relatively slowly, so that the melting point may not be accurately detected using TG-DTA or DSC.

[0004] Therefore, for inorganic oxides, it is considered to measure the softening point at which the shape of the inorganic oxide begins to change as an index having the same meaning as the melting point. Thermomechanical analysis (hereinafter, also referred to as TMA) is one method for measuring the softening point (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 01-274033 Summary of the Invention [Problem to be solved by the invention]

[0006] However, even if the collected inorganic oxide sample is directly subjected to TMA to measure the softening point, the measurement may not be reproducible. Since inorganic oxide samples are, for example, in the form of chips and have different sizes and shapes, these differences can significantly affect the softening point measurement by TMA and can impair reproducibility.

[0007] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a technique for measuring the softening point of an inorganic oxide sample with high accuracy and high reproducibility. [Means for solving the problem]

[0008] The first aspect of the present invention is A preparation step of preparing an inorganic oxide sample; grinding the inorganic oxide sample to form a powder sample; a step of filling the powder sample into a heat-resistant container having an opening and placing a pressing lid having an area of ​​0.3 to 0.9 times the area of ​​the opening; a measuring step of subjecting the heat-resistant container filled with the powder sample to a thermomechanical analysis device, heating the powder sample while applying a load from above the pressing lid, thereby obtaining a thermomechanical analysis curve showing the relationship between the temperature of the powder sample and the change in position of the pressing lid due to thermal deformation, and measuring the softening point of the inorganic oxide sample based on the thermomechanical analysis curve. A method for measuring an inorganic oxide sample is provided.

[0009] The second aspect of the present invention is the method according to the first aspect, In the measurement process, a thermomechanical analysis differential curve showing the relationship between the temperature of the powder sample and the differential coefficient of the position of the push cap due to thermal deformation is obtained together with the thermomechanical analysis curve, and the median value of the temperatures at which the differential coefficient becomes constant after the position of the push cap begins to descend in the thermomechanical analysis differential curve is defined as the softening progression temperature, and the temperature of the intersection between the tangent to the thermomechanical analysis curve at the softening progression temperature and the extension of the horizontal part of the thermomechanical analysis curve before the position of the push cap descends is measured as the softening point.

[0010] A third aspect of the present invention is the method according to the first or second aspect, The particle size of the powder sample is 43 μm or less.

[0011] A fourth aspect of the present invention is the method according to any one of the first to third aspects, In the measuring step, the temperature rise rate is set to 3° C. / min or more and 30° C. / min or less.

[0012] A fifth aspect of the present invention is the method according to any one of the first to fourth aspects, In the measuring step, the load is set to 3 kPa or more and 200 kPa or less. Effect of the Invention

[0013] According to the present invention, the softening point of an inorganic oxide sample can be measured with high accuracy and reproducibility. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a diagram showing a flow diagram of a measurement method for an inorganic oxide sample according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram illustrating a sample container according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic diagram of a thermomechanical analyzer. [Figure 4] FIG. 4 is a diagram showing a thermomechanical analysis curve and a thermomechanical analysis differential curve obtained for Sample 1 of Example 1. [Diagram 5]FIG. 5 is a diagram showing a thermomechanical analysis curve and a thermomechanical analysis differential curve obtained for Sample 2 in Example 1. [Figure 6] FIG. 6 is a diagram showing a thermomechanical analysis curve and a thermomechanical analysis differential curve obtained for Sample 3 in Example 1. [Figure 7] FIG. 7 is a diagram showing a thermomechanical analysis curve and a thermomechanical analysis differential curve obtained in Example 2. [Figure 8] FIG. 8 is a diagram showing a thermomechanical analysis curve and a thermomechanical analysis differential curve obtained in Example 3. [Figure 9] FIG. 9 is a diagram showing a thermomechanical analysis curve and a thermomechanical analysis differential curve obtained for Sample 1 of Comparative Example 1. [Figure 10] FIG. 10 is a diagram showing a thermomechanical analysis curve and a thermomechanical analysis differential curve obtained for Sample 2 of Comparative Example 1. [Figure 11] FIG. 11 is a diagram showing a thermomechanical analysis curve and a thermomechanical analysis differential curve obtained for Sample 3 of Comparative Example 1. [Figure 12] FIG. 12 is a diagram showing a thermomechanical analysis curve obtained in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] <Findings Obtained by the Inventors> When measuring inorganic oxide samples in the form of flakes using TMA, the heating conditions are not uniform for each inorganic oxide sample due to differences in size and shape, which can greatly affect the temperature at which the inorganic oxide sample begins to soften. As a result, the softening points obtained by the measurement can vary greatly. In addition, inorganic oxides generally have low thermal conductivity, so melting can progress all at once due to the stored heat. At that time, the measurement position can change drastically due to the influence of the shape, and sometimes it becomes impossible to measure the softening point itself. After examining this point, we focused on crushing inorganic oxide samples into powder. By making them into powder samples, the differences in size and shape of inorganic oxide samples can be averaged out, and the heating conditions in TMA can be uniform. In addition, it is possible to avoid situations where measurements are impossible due to the influence of the shape.

[0016] However, even when a powder sample is measured by TMA, the softening point of the inorganic oxide sample may not be measured accurately and reproducibly. This is because the softening point cannot be determined accurately due to noise generated in a thermomechanical analysis curve (hereinafter, also referred to as a TMA curve) obtained by TMA measurement, which shows the relationship between temperature and the change in measurement position due to thermal deformation. This point will be specifically explained with reference to Figure 3. Figure 3 is a schematic diagram of a thermomechanical analyzer.

[0017] As shown in FIG. 3, the thermomechanical analysis device (TMA device) 100 includes a probe 20 that is in contact with the sample container 10', a load generating unit 30 that is connected to the probe 20 and applies a load to the push lid 12', a displacement detecting unit 40 that detects the amount of displacement of the probe 20, and a heater 50 that is arranged around the sample container 10' and heats the powder sample S. The sample container 10' includes a heat-resistant container 11' that has an opening and contains the powder sample S, and a push lid 12' that covers the opening. In the TMA device 100, the powder sample S is heated by the heater 50 while the load generating unit 30 applies a predetermined load to the powder sample S via the probe 20. Then, while the heater 50 heats the powder sample S at a predetermined temperature rise rate, the displacement detecting unit 40 measures the change in the position of the push lid 12' due to the deformation of the powder sample S. Then, the change in the position of the push lid 12' due to the thermal deformation of the powder sample S according to the temperature is obtained as a TMA curve.

[0018] Noise in the TMA curve of a powder sample obtained by pulverizing an inorganic oxide sample is caused by repeated up-and-down movements of the probe 20. Further investigation into this noise has revealed that the repeated up-and-down movements of the probe 20 are caused by gas generated from the powder sample S. The powder sample S may generate gas when melted by heating. When the sample container 10' is sealed with the press lid 12', the gas generated by heating may suddenly lift the press lid 12' and the probe 20, and when the gas escapes from the sample container 10', the probe 20 may suddenly drop. This up-and-down movement of the probe 20 is likely to occur when the inorganic oxide sample begins to soften, so the softening point of the inorganic oxide sample may not be measured accurately and with high reproducibility.

[0019] Therefore, the inventors have conducted research to suppress the vertical movement of the probe caused by gas generated from the powder sample, and have found that it is effective to set the pressing lid of the sample container to a predetermined area ratio smaller than the area of ​​the opening of the sample container. By configuring the sample container in this way so that gas can be constantly released, it is possible to suppress the deterioration of measurement accuracy and reproducibility caused by gas.

[0020] The present invention has been made based on the above findings.

[0021] <One embodiment of the present invention> The method for measuring an inorganic oxide sample according to one embodiment of the present invention will be described below with reference to the drawings. Fig. 1 is a diagram showing a flow diagram of the method for measuring an inorganic oxide sample according to one embodiment of the present invention. The method for measuring an inorganic oxide sample according to this embodiment includes a preparation step, a crushing step, a filling step, and a measurement step. Each step will be described in detail below.

[0022] (Preparation process S1) First, an inorganic oxide sample to be measured is prepared.

[0023] The inorganic oxide sample is a reduction product (mainly slag) obtained by reduction of Ni oxide ore such as saprolite. The inorganic oxide sample contains inorganic oxide and metal components, and is composed of metals scattered in the inorganic oxide. The metal components in the inorganic oxide sample are metals such as Fe-Ni alloys. The nonmetallic material contained in the reduction product is slag, and the compound form is, for example, Fe2O3, Al2O3, CaO, MgO, SiO2, etc. In the reduction process, the metal component particles scattered in the semi-molten slag are bonded together to recover the coarsened metal component particles. Here, if a slag with a low melting point and low viscosity is generated, the metal component particles can be coarsened more, and the recovery rate of the metal components can be increased. Therefore, in inorganic oxide samples, it is important to measure the softening point as an index having the same meaning as the melting point.

[0024] (Crushing process S2) Next, the inorganic oxide sample is pulverized to form a powder sample. As described above, the inorganic oxide sample is in the form of chips, and differences in size and shape may hinder the measurement of the softening point. In this regard, by forming the sample into a powder, differences in size and shape between different inorganic oxide samples can be eliminated.

[0025] The particle size of the powder sample is not particularly limited as long as it can eliminate the difference in size and shape of the inorganic oxide sample. From the viewpoint of more stable improvement of the measurement accuracy and measurement reproducibility, the particle size of the powder sample is preferably 43 μm or less. The lower limit is not particularly limited, but it is preferable that it is 1 μm, for example. The powder sample is selected, for example, using a sieve with a specified mesh size, and the particle size indicates the maximum particle size.

[0026] The method for pulverizing the inorganic oxide sample is not particularly limited, and any known method can be used, for example, a vibrating mill.

[0027] (Filling process S3) Next, in order to provide the powder sample S to the TMA apparatus 100, a sample container 10 for accommodating the powder sample S is prepared as shown in Fig. 2. Fig. 2 is a schematic diagram for explaining the sample container 10 according to one embodiment of the present invention.

[0028] In this embodiment, as shown in FIG. 2, a sample container 10 is used that includes a heat-resistant container 11 with an opening at the top and a press lid 12 that has an area that is 0.3 to 0.9 times the area of ​​the opening.

[0029] By making the area of ​​the push lid 12 0.9 times or less the area of ​​the opening of the heat-resistant container 11, it is possible to release the gas generated from the powder sample S to the outside of the sample container 10 without covering the entire opening with the push lid 12. This makes it possible to suppress the up and down movement of the probe 20 due to gas generation in the TMA curve and reduce noise. In addition, when the powder sample S melts, the melt overflows from the gap between the heat-resistant container 11 and the push lid 12. At that time, since the viscosity of the melt is high, if the gap between the heat-resistant container 11 and the push lid 12 is narrow, the melt cannot be made to overflow quickly, and the melt will remain under the push lid 12. In that case, even if the powder sample S melts, the position of the push lid 12 will not drop, so the detection of the softening point will be delayed or will become impossible to determine. In this regard, by making the area 0.9 times or less, the influence of the remaining melt can be suppressed, and the measurement accuracy and reproducibility can be improved. On the other hand, by making the area of ​​the press lid 12 0.3 times or more the area of ​​the opening, it is possible to suppress the application of localized load to the powder sample S and obtain accurate information on the amount of displacement accompanying the thermal deformation of the powder sample S. The area ratio of the press lid 12 to the opening may be 0.3 times or more and 0.9 times or less, and is preferably 0.7 times or more and 0.9 times or less.

[0030] In the sample container 10, the materials of the heat-resistant container 11 and the press lid 12 are not particularly limited as long as they are heat-resistant so as not to melt and deform during measurement in the TMA device 100. For example, alumina, platinum, etc. can be used as the material of the sample container 10. The material of the sample container 10 may be appropriately changed depending on the components constituting the inorganic oxide sample. For example, when the inorganic oxide sample contains a large amount of calcium oxide, calcium oxide may corrode alumina, so a sample container made of platinum is preferably used.

[0031] The shape of the press lid 12 is not particularly limited as long as it can form a gap between the press lid 12 and the opening of the heat-resistant container 11. For example, a hexagonal shape is preferable.

[0032] The size of the heat-resistant container 11 may be appropriately adjusted so that it can be used in the TMA device 100. The size of the press lid 12 may be appropriately changed depending on the size of the opening of the heat-resistant container 11.

[0033] Next, the powder sample S is filled into the heat-resistant container 11, and the pressing lid 12 is placed on the powder sample S. The filling method is not particularly limited as long as the powder sample S can be densely packed into the heat-resistant container 11. For example, after the powder sample S is placed in the heat-resistant container 11, it is preferable to tamp it down by pressing it with a rod-shaped member or the like.

[0034] (Measurement process S4) Next, a heat-resistant container 11 filled with a powder sample S and having a press lid 12 placed thereon is provided to the TMA device 100 as the sample container 10. In the TMA device 100, the sample container 10 is heated while a load is applied from above the press lid 12 of the sample container 10. At this time, by heating at a predetermined temperature increase rate, the change in position of the press lid 12 due to the thermal deformation of the powder sample S is measured. As a result, a thermomechanical analysis curve (TMA curve) showing the relationship between temperature and the change in position of the press lid 12 is obtained.

[0035] As shown in FIG. 4, the TMA curve has a horizontal axis of temperature [°C] and a vertical axis of change in the position of the press lid 12 [μm]. In FIG. 4, the TMA curve is shown as a relatively thick curve. When the temperature is below the softening point, the powder sample S is not easily deformed by heat, so the TMA curve is horizontal. When the temperature approaches the softening point, the powder sample S begins to deform by heat. As a result, the position of the press lid 12 gradually drops, so the TMA curve drops in a curved shape. Then, when the temperature reaches or exceeds the softening point, the powder sample melts, causing a sudden change in the position of the press lid 12, and the TMA curve drops sharply.

[0036] Since the powder sample S is measured in the obtained TMA curve, the influence of differences in size and shape of the inorganic oxide sample can be reduced, and the relationship between the inherent temperature of the inorganic oxide constituting the powder sample S and the position of the pressing lid 12 can be reflected. In addition, noise due to gas generated from the powder sample S can also be suppressed. Therefore, the softening point of the inorganic oxide sample can be measured with high accuracy and high reproducibility based on the TMA curve. The softening point of the inorganic oxide sample can be detected, for example, at the temperature when the position of the pressing lid 12 starts to descend in the TMA curve.

[0037] From the viewpoint of measuring the softening point of the powder sample S more accurately, it is preferable to measure the softening point based on a thermomechanical analysis differential curve (hereinafter also referred to as a TMA differential curve) showing the relationship between the temperature of the powder sample and the differential coefficient of the position of the push lid 12 accompanying the thermal deformation, together with the TMA curve. Specifically, in the TMA differential curve, the median value of the temperatures at which the differential coefficient becomes constant after the position of the push lid 12 starts to descend is defined as the softening progress temperature, and it is preferable to determine the temperature of the intersection between the tangent at the softening progress temperature of the TMA curve and the extension of the horizontal part of the TMA curve before the position of the push lid 12 descends as the softening point of the powder sample S. In the TMA differential curve, the horizontal axis indicates temperature [°C] and the vertical axis indicates the displacement amount per unit time [μm / s]. In FIG. 4, the TMA differential curve is illustrated with a line thinner than the TMA curve indicated by a thick line. The TMA differential curve has a point where the displacement amount per unit time decreases at a predetermined temperature near the softening point and then becomes horizontal. That is, in the TMA curve, there is a point where the position of the push lid 12 drops linearly after it drops near the softening point. The median of the temperatures at which the differential coefficient becomes constant, that is, the median of the temperatures at which the TMA differential curve becomes horizontal, is defined as the softening progress temperature, and the temperature at the intersection of the tangent of the TMA curve at the softening progress temperature and the extension of the horizontal part of the TMA curve before the position of the push lid 12 drops is defined as the softening point, so that the softening point of the powder sample S can be measured with high accuracy and reproducibility. The extension of the horizontal part of the TMA curve before the position of the push lid 12 drops should be drawn horizontally so that it is in contact with the range where the position of the push lid 12 does not change or the displacement of the position of the push lid 12 is small in the temperature range lower than the softening point. Note that the horizontal axis of the TMA curve is temperature and the vertical axis is position, so the vertical axis of the TMA differential curve is the displacement of the position per unit temperature [μm / ℃], but since the heating rate is constant, it is expressed as the displacement per unit time [μm / s].

[0038] Regarding the measurement conditions of the measurement step S4, the load and the temperature rise rate are not particularly limited. From the viewpoint of reducing the influence of the gas generated from the powder sample S described above, it is preferable to use a heavy load and a slow temperature rise rate. By using a heavy load, the up and down movement of the press lid 12 caused by the gas can be further suppressed. By using a slow temperature rise rate, the sudden thermal deformation of the powder sample S and the associated gas generation can be suppressed, and the up and down movement of the press lid 12 caused by the gas can be suppressed. The temperature rise rate is preferably 3°C / min or more and 30°C / min or less. The load applied to the powder sample S is preferably 3 kPa or more and 200 kPa or less.

[0039] In this manner, the softening point of the inorganic oxide sample can be measured.

[0040] <Effects of this embodiment> According to this embodiment, one or more of the following advantages are achieved.

[0041] In this embodiment, an inorganic oxide sample is crushed, and the resulting powder sample S is filled into a sample container 10. At this time, a sample container 10 including a heat-resistant container 11 having an opening and a push lid 12 having an area of ​​0.3 to 0.9 times the area of ​​the opening is used. Then, the sample container 10 filled with the powder sample S is provided to the TMA device 100, and the powder sample S is heated while applying a load from above the push lid 12, thereby obtaining a TMA curve showing the relationship between the temperature and the change in the position of the push lid 12 due to the thermal deformation of the powder sample S. In this measurement, by using the powder sample S as the inorganic oxide sample, it is possible to suppress the difference in the change in the position of the push lid 12 due to the difference in the size and shape of the inorganic oxide sample in the TMA curve. In addition, it is possible to avoid a situation in which measurement is impossible due to the influence of the shape. In addition, by making the push lid 12 smaller than the opening, it is possible to suppress the repeated up and down movement of the probe 20 due to the gas generated by the melting of the powder sample S, and to reduce the occurrence of noise in the TMA curve. Furthermore, by making the push lid 12 smaller than the opening so that the molten material quickly spills out, it is possible to prevent the detection of the softening point from being delayed or becoming impossible to distinguish. In other words, it is possible to prevent the reflection of noise due to differences in size and shape of the inorganic oxide sample or gas generation in the TMA curve. As a result, the softening point of the inorganic oxide constituting the powder sample S can be measured with high accuracy and high reproducibility based on the TMA curve.

[0042] In the measurement step S4, it is preferable to obtain a TMA differential curve together with the TMA curve, and measure the softening point based on these. Specifically, first, in the TMA differential curve, the median of the temperatures at which the differential coefficient becomes constant after the position of the push lid 12 starts to move down is determined as the softening progress temperature. Next, a tangent line at the softening progress temperature of the TMA curve is drawn, and an extension line of the horizontal part of the TMA curve before the position of the push lid 12 moves down is drawn. Then, the temperature at the intersection of these tangent lines and the extension line is defined as the softening point of the powder sample S. Although the softening point defined in this way is merely a relative value, it is highly correlated with the melting point inherent to the inorganic oxide, and the softening point of the inorganic oxide can be grasped more accurately and with higher reproducibility.

[0043] In the crushing step S2, it is preferable to crush the inorganic oxide sample so that the particle size of the powder sample S becomes 43 μm or less. With such a powder sample S, the influence of differences in size and shape on the measurement value can be eliminated, and the softening point of the inorganic oxide can be measured with higher accuracy and reproducibility.

[0044] In the measurement step S4, the temperature rise rate is preferably set to 3° C. / min or more and 30° C. / min or less. By performing the measurement at such a temperature rise rate, it is possible to suppress abrupt melting of the powder sample S and suppress noise due to gas in the TMA curve.

[0045] In the measurement step S4, the load is preferably set to 3 kPa or more and 200 kPa or less. By applying such a load while heating, noise due to gas generation in the TMA curve can be more reliably suppressed.

[0046] Although an embodiment of the present invention has been described above, the present invention is not limited to the above-described embodiment, and various modifications can be made without departing from the spirit of the present invention. EXAMPLES

[0047] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0048] Example 1 In Example 1, slag obtained by reduction treatment of Ni oxide ore was prepared as an inorganic oxide sample. 5 g of this slag was weighed out and crushed in a disk-type vibration mill to form a powder sample with a particle size of 43 μm or less. This powder sample was placed in an alumina pan (diameter 5 mm, height 5 mm) which is a heat-resistant container. Then, a rod-shaped member with a diameter of 4 mm was pressed into the alumina pan several times to compact the powder sample, and the powder sample was filled into the alumina pan. Then, a hexagonal alumina bolt of M2 was placed on the filled powder sample as a pressing lid with its head facing downward. The area of ​​the alumina bolt was 0.8 times the area of ​​the opening of the alumina pan.

[0049] Next, the sample container, which was filled with the powder sample in an alumina pan and had the lid pressed with an alumina bolt, was introduced into a thermomechanical analyzer ("TMA-4000SA" manufactured by Netsch Japan Co., Ltd.) and measurements were performed. The measurement conditions were a load of 10g (6kPa) and a heating rate of 20℃ / min. A TMA curve showing the relationship between temperature and the displacement of the powder sample was obtained. In addition, the TMA curve was differentiated to obtain a TMA differential curve showing the relationship between temperature and the displacement per unit time.

[0050] In this example, samples 1 to 3 were taken from the same slag, and measurements were performed using a TMA device to obtain TMA curves and TMA differential curves, which are shown in Figures 4 to 6.

[0051] As shown in Figure 4, the temperature at which the displacement per unit time becomes horizontal (softening progress temperature) was determined to be 1278°C from the TMA differential curve. A tangent line was drawn on the TMA curve that touches the softening progress temperature. An extension line was also drawn so as to touch the point on the TMA curve where the curve becomes horizontal below the softening point. The softening point of the slag was confirmed to be 1193°C from the temperatures at the intersections of the tangent lines and the extension lines.

[0052] Tangents were similarly drawn for Figures 5 and 6. In Figure 5, the softening progress temperature was 1265°C, and the softening point of the slag was confirmed to be 1187°C from the temperature at the intersection of the tangent and the extended line. In Figure 6, the softening progress temperature was 1280°C, and the softening point of the slag was confirmed to be 1188°C from the temperature at the intersection of the tangent and the extended line.

[0053] As described above, in Example 1, the softening points measured for Samples 1 to 3 were 1193° C., 1187° C., and 1188° C., respectively, and it was confirmed that the softening points could be measured with high accuracy and high reproducibility.

[0054] Example 2 In Example 2, a sample was taken from a slag different from that in Example 1, and a TMA curve and a differential TMA curve were obtained in the same manner as in Example 1, except that the load applied to the powder sample during measurement with the TMA device was changed from 10 g (6 kPa) to 100 g (60 kPa). These are shown in Figure 7.

[0055] In Example 2, the softening point of the slag was confirmed to be 1141° C. The slag used in Example 2 generated noise due to gas generated from the powder sample when melted by heating. However, it was confirmed that the softening point could be measured with high accuracy and reproducibility without being affected by noise by applying a load of 100 g to the powder sample.

[0056] Example 3 In Example 3, a different sample was taken from the same slag as in Example 2, and a TMA curve and a differential TMA curve were obtained in the same manner as in Example 1, except that the heating rate was changed from 20°C / min to 5°C / min when measuring with the TMA device. These are shown in Figure 8.

[0057] In Example 3, the softening point of the slag was confirmed to be 1138°C. The slag used in Example 3 had noise due to gas generated from the powder sample when melted by heating, but the softening point could be measured without being affected by noise by setting the heating rate to 5°C / min. In addition, since the softening point was the same as in Example 2, it was confirmed that the softening point could be measured with high accuracy and high reproducibility.

[0058] Comparative Example 1 In Comparative Example 1, the slag was not crushed, but the pieces were sandwiched between anti-fusing plates (alumina plates) and then introduced into the TMA for measurement. The TMA curve and the TMA differential curve were obtained in the same manner as in Example 1. In Comparative Example 1, Samples 1 to 3 were taken from the same slag other than those in Examples 1 and 2, and measurements were performed three times. These are shown in Figures 9 to 11.

[0059] As shown in Figs. 9 to 11, it was confirmed that the TMA curves of Samples 1 to 3 of Comparative Example 1 were different, and that the temperatures at which the slag began to soften and the position of the fusion prevention plate changed significantly were different. It was also confirmed that the position of the fusion prevention plate changed suddenly at a certain temperature in each TMA curve. In these samples, it was not possible to determine the softening progress temperature as in Examples 1 to 3. If the temperature of the intersection of the extension line of the vertical part where the position of the fusion prevention plate suddenly drops and the extension line of the horizontal part before the position of the fusion prevention plate drops is considered as the provisional softening point, the provisional softening points of Samples 1 to 3 were 1331.5°C, 1318.9°C, and 1176.8°C, respectively. From this, it was confirmed that it was impossible to measure the softening points, and even if a provisional softening point was determined, the provisional softening points would vary despite being the same sample, and even the provisional softening points could not be measured with high reproducibility. This is thought to be because the size and shape of the slag pieces used in each sample were not identical, and these differences made it impossible to measure the displacement when the slag began to soften with high accuracy and reproducibility.

[0060] Comparative Example 2 In Comparative Example 2, a sample was taken from a slag different from those in Examples 1, 2, and Comparative Example 1, and the sample was introduced into the TMA apparatus using an alumina pin that covered the opening of the alumina pan instead of a pressing lid (alumina bolt) with an area smaller than the opening of the alumina pan, and a TMA curve was obtained in the same manner as in Example 1. This is shown in FIG.

[0061] As shown in Fig. 12, in the TMA curve of Comparative Example 2, the powder sample started to soften, the position of the alumina pin dropped, and then the position changed up and down, confirming the influence of noise. This noise is considered to be due to the alumina pin being lifted suddenly by the gas generated when the powder sample melted, and then being lowered suddenly when the gas escaped. In Fig. 12, it was confirmed that although the softening point of the powder sample could be measured as 1293°C, the measurement could not be performed accurately due to noise.

[0062] As described above, the softening point of an inorganic oxide sample can be measured with high accuracy and reproducibility by crushing an inorganic oxide sample into powder and filling it into a heat-resistant container, placing a press lid with an area smaller than the opening of the heat-resistant container on it, and subjecting it to a TMA device for measurement. [Explanation of symbols]

[0063] 10 Sample container 11 Heat-resistant containers 12 Press Lid 20 Probe 30 Load generating part 40 Displacement detection unit 50 Heater 100 Thermomechanical analyzer

Claims

1. A preparation step of preparing an inorganic oxide sample; grinding the inorganic oxide sample to form a powder sample; a filling step of filling the powder sample into a heat-resistant container having an opening and placing a pressing lid having an area of ​​0.3 to 0.9 times the area of ​​the opening; a measuring step of subjecting the heat-resistant container filled with the powder sample to a thermomechanical analysis device, heating the powder sample while applying a load from above the pressing lid, thereby obtaining a thermomechanical analysis curve showing the relationship between the temperature of the powder sample and the change in position of the pressing lid due to thermal deformation, and measuring the softening point of the inorganic oxide sample based on the thermomechanical analysis curve. Measurement method for inorganic oxide samples.

2. In the measurement step, a thermomechanical analysis differential curve showing the relationship between the temperature of the powder sample and the differential coefficient of the position of the pressing lid due to thermal deformation is obtained together with the thermomechanical analysis curve, the median value of the temperatures at which the differential coefficient becomes constant after the position of the pressing lid starts to lower in the thermomechanical analysis differential curve is defined as the softening progress temperature, and the temperature of the intersection between the tangent at the softening progress temperature of the thermomechanical analysis curve and the extension of the horizontal part of the thermomechanical analysis curve before the position of the pressing lid lowers is measured as the softening point. The method for measuring an inorganic oxide sample according to claim 1.

3. The particle size of the powder sample is 43 μm or less. The method for measuring an inorganic oxide sample according to claim 1 or 2.

4. In the measurement step, the temperature rise rate is set to 3° C. / min or more and 30° C. / min or less. The method for measuring an inorganic oxide sample according to claim 1 or 2.

5. In the measurement step, the load is set to 3 kPa or more and 200 kPa or less. The method for measuring an inorganic oxide sample according to claim 1 or 2.

Citation Information

Patent Citations

  • Thermomechanical analysis

    JP1989274033A